Exploring the Utilization of Augmented Reality in Higher Education Perceptions of Media and Communication Students - Sawsan Taha; Enas Abulibdeh; Juman Qunais; Huda Skaik; Emad M. Alghazo; Sumaya Daoud; Abdeldjalil Bouzenoun (Emerging Science Journal, 2023)
The present study aims to explore the perceptions and usage of Augmented Reality (AR) technology among media students in Palestinian universities. A quantitative approach was adopted, and data was gathered from a web-based survey of 237 media students. The Technology Acceptance Model (TAM) was utilized to gauge participants' perceptions of AR, and descriptive statistics were used for analysis. The findings reveal a generally positive perception of AR as a beneficial tool for skill enhancement, with mean scores ranging from 3.70 to 4.04 indicating strong agreement. The study also found moderate to high AR usage among participants, particularly for translating texts using Google Translate, but noted that usage patterns were more individual-oriented. Additionally, 91.1% of respondents attributed the COVID-19 pandemic to increased technology usage in higher education. The novelty of this study lies in providing insights into the perception and application of AR in higher education within the Palestinian context, an under-researched area. The study sheds light on the potential for integrating AR more formally into curricula, which could foster a more engaging and immersive educational experience. However, it also highlights the need to address barriers such as lack of technical support and possible discomfort with technology. Doi: 10.28991/ESJ-2023-SIED2-016 Full Text: PDF